Addressing the Challenge of Mathematical Misconceptions: Development of Interactive Multimedia Based on Cognitive Conflict Strategy - Winarso, Widodo; Toheri; Tamsik Udin (Journal of Education Technology, 2023)
Mathematical misconceptions hinder students' learning and understanding of mathematical concepts. This study aims to analyze the issue of mathematical misconceptions by developing interactive multimedia based on the cognitive conflict strategy. The research design used was research and development with Design-Based Research (DBR), combining qualitative and quantitative data collection techniques. There were fourteen participants in this study including students, teachers, and expert validators, and the research procedure involved the implementation of interactive multimedia interventions. Data collection techniques had pretest and posttest assessments after the intervention, observations, and interviews. The research data were analyzed using the Paired Sample t-Test. The study's findings indicated that the interactive multimedia intervention based on the cognitive conflict strategy effectively reduced students' mathematical misconceptions. The results also demonstrated improved conceptual understanding and increased engagement in the learning process. This research contributes to the field of mathematics education by presenting innovative and practical solutions to address students' misconceptions. The research implications suggest that interactive multimedia based on the cognitive conflict strategy can be used as a pedagogical approach to promote conceptual understanding and reduce mathematical misconceptions.